A comparison of tetanus antibody levels between patients with high body mass indices and normal patients - Ince, Nevin; Onmez, Attila; Caliskan, Emel (Annals of Medical Research, 2021)
Aim: It has recently been thought that obesity may cause metabolic diseases as well as being linked to immune system dysfunction. The purpose of this study was to compare tetanus antibody levels between patients with high body mass indices and healthy-weight individuals and to examine the effect of obesity on tetanus antibody levels in adults. Materials and Methods: This cross-sectional research was performed at Duzce University,Faculty of Medicine from December 2018 to February 2019. The study group was composed of obese patients who had undergone tetanus immunization within the previous 10 years. The control group consisted of healthy-weight individuals who had also been immunized in the previous 10 years. An enzyme-linked immunosorbent assay kit (Euroimmun, Germany) was used to detect antibodies to tetanus toxoid. Results: Sixty-seven individuals with obesity and 21 controls participated in this study. Anti-tetanus IgG antibodies were at protective levels in both groups, although the mean antibody level in the patients with obesity was significantly lower compared to the control group (0.788±0.602 vs 1.112±0.398, p=0.022). Anti-tetanus IgG antibodies were significantly negatively correlated with BMI (r=-0.269, p=0.016). Conclusion: The detection of low levels of tetanus antibody titers in patients with high BMI in this study compared to the control group suggests that greater attention is required in this population.